-42=-6b

Simple and best practice solution for -42=-6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -42=-6b equation:


Simplifying
-42 = -6b

Solving
-42 = -6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6b' to each side of the equation.
-42 + 6b = -6b + 6b

Combine like terms: -6b + 6b = 0
-42 + 6b = 0

Add '42' to each side of the equation.
-42 + 42 + 6b = 0 + 42

Combine like terms: -42 + 42 = 0
0 + 6b = 0 + 42
6b = 0 + 42

Combine like terms: 0 + 42 = 42
6b = 42

Divide each side by '6'.
b = 7

Simplifying
b = 7

See similar equations:

| 5x^2-20x=10 | | 2(3a+12)=3(4a+2) | | 3c=-18 | | y^2+18y+32=226 | | 6x+5=2x-11 | | t-19=-2(t+5) | | z-6=-10 | | v^2-20v+19=0 | | p-22=3(2p-4) | | 6x-5=2x-11 | | -4+a=15 | | 6x+7y=13 | | 12x+5=8x+13 | | 2y-6=9-3y | | w^2+6w=-3 | | log(y)=1.6 | | 4=m+19 | | 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 | | -x-2/7=x+1/6+4/7 | | 12x-18=10x+10 | | 5c-4b= | | 4n+1-5n=6n+7-9n | | 4b+8=7b-4 |

Equations solver categories